2013
DOI: 10.1111/1469-0691.12143
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Acinetobacter baumannii isolates from paediatric cancer patients in Egypt

Abstract: Acinetobacter baumannii is an important nosocomial pathogen, commonly causing infections in immunocompromised patients. It is increasingly reported as a multidrug-resistant organism, which is alarming because of its capability to resist all available classes of antibiotics including carbapenems. The aim of this study was to examine the genetic and epidemiological diversity of A. baumannii isolates from paediatric cancer patients in Egypt, by sequencing the intrinsic blaOXA -51-like gene, genotyping by pulsed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
56
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 28 publications
14
56
4
Order By: Relevance
“…In this studybla OXA-23 gene was most common virulent oxacillinase gene detected among carbepenem resistant A. baumannii, this in agreement with many studies reported that bla OXA-23 was the most frequent type of carbapenamase identified (Al agamy et al, 2013;Cicek et al, 2013;Abbot et al, 2013;Al Hassan et al, 2013;Fouad et al, 2013). The percentage of bla OXA-23 -like gene detected in impenem resistant isolates were 69.7% (23/33), this result is in agreement with Zowawi et al, 2015;Luo et al, 2015, different percentages of presence of bla OXA-et al, 2013), 100% by Fouad et al 2013, and others also reported all over the world as those reported by Cherkaoue et al, 2015(51.8%), Val et al, 2015(85%), 85.7% ElAbd et al, 2014and 100% Rolain et al, 2016 None of the impenem resistant isolates were positive for bla OXA-24 -like or bla OXA-58 -like genes this result was in agreement with Rolain et al, (2016).…”
Section: Resultssupporting
confidence: 89%
“…In this studybla OXA-23 gene was most common virulent oxacillinase gene detected among carbepenem resistant A. baumannii, this in agreement with many studies reported that bla OXA-23 was the most frequent type of carbapenamase identified (Al agamy et al, 2013;Cicek et al, 2013;Abbot et al, 2013;Al Hassan et al, 2013;Fouad et al, 2013). The percentage of bla OXA-23 -like gene detected in impenem resistant isolates were 69.7% (23/33), this result is in agreement with Zowawi et al, 2015;Luo et al, 2015, different percentages of presence of bla OXA-et al, 2013), 100% by Fouad et al 2013, and others also reported all over the world as those reported by Cherkaoue et al, 2015(51.8%), Val et al, 2015(85%), 85.7% ElAbd et al, 2014and 100% Rolain et al, 2016 None of the impenem resistant isolates were positive for bla OXA-24 -like or bla OXA-58 -like genes this result was in agreement with Rolain et al, (2016).…”
Section: Resultssupporting
confidence: 89%
“…Among them, 125 isolates (95.4%) were MHT positive, and 59/150 isolates (39.3%) were IECT positive. In Egypt, there have been few reports describing the emergence of the bla OXA-23 gene among A. baumannii isolates (12)(13)(14) and one report of an NDM-2 carbapenemase isolate from a patient transferred to Germany from an Egyptian hospital (15). Herein, we found that 115/ 150 (76.7%) isolates were bla OXA-23 -like positive and 150/150 (100%) were bla OXA51 -like positive.…”
mentioning
confidence: 59%
“…This could be due to transfer of cases from different wards in the hospital to the ICU. The plasticity of Acinetobacter genetic composition allow easy inclusion of new genes, thus making it difficult to define its origin (Al-Hassan et al, 2013). Similarly, in a previous study done on Egyptian pediatric cancer patients, diversity of A. baumannii isolates was confirmed (Al-Hassan et al, 2013).…”
Section: Resultsmentioning
confidence: 94%